BALINESE TRADITIONAL TREATMENT (BALIAN) IN PATIENTS WITH MENTAL DISORDERS - Ni Made Sri Muryani; Indah Winarni; Setyoadi Setyoadi (Belitung Raya Foundation, Indonesia, 2018)
Background: Balinese believe that mental disorders are caused after being possessed and cursed by one’s ancestors, so Balinese choose traditional Balinese treatment (balian/shaman) in handling patients with mental disorders. Objective: The purpose of this research was to explore deeply about the use of balian in treating patients with mental disorder. Methods: A qualitative method with an interpretive phenomenological approach was used. In-depth interview technique with semi-structured interview guidelines was used for data collection. Data were analyzed using Interpretative Phenomenological Analysis (IPA) approach. Results: Five themes emerged, including 1) ancestors’ curse, 2) possessed by a spirit, 3) believe that balian has healing power, 4) balian becomes the first choice prior to the hospital, and 5) the use of traditional and medical treatment at once. Conclusion: Balian became the first choice in treating patients with mental disorders. It is because Balinese still believes that mental disorders caused by the ancestors’ curse and possessed by the spirit.